(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Anxiety and depression are among the most prevalent psychiatric problems that can be associated with patients’ physical issues and illnesses. Consequently, the current study aimed to investigate the effect of anxiety and early depression on the chances of contracting the COVID-19 infection among the personnel of outpatient hospitals. Thus, 241 members (136 male and 105 female employees) of the personnel in Moharrari Hospital, Iran, took part in the study and returned the DASS-21 questionnaire. Moreover, follow-up procedures lasted for a year. Out of the overall sample, 62 members contracted the COVID-19 in that year, and 6 members were hospitalized. The findings indicated that the contraction rate of the people who had scored higher in terms of depression and anxiety was significantly higher than that of the people with no symptoms of depression and anxiety. Moreover, the findings showed that having a history of physical illnesses had a significant relationship with anxiety and depression. Finally, no significant difference was observed between men and women in terms of suffering from depression and anxiety. The findings implied that psychiatric and physical problems can have mutual relationships with each other, and considering it can help select and develop more effective and optimal interventions.